Effects of functional massage on spasticity and motor functions in children with cerebral palsy: a randomized controlled study - Bingöl, Hasan; Yılmaz, Özlem Özbek (My University, 2018)
Purpose: The purpose of this study was to investigate the effects of functional massage on the severity of lower limb spasticity and gross motor function of children with cerebral palsy (CP). Methods: In this study, 20 children who were classified as level I-IV according to Gross Motor Classification System (GMFCS), who had communication skills (according to Communication Function Classification System, level I-III), who had never undergone surgery and who were between the ages of 5-12 years, were recruited from two rehabilitation centers. Children were randomized to control or experimental groups to receive either only Traditional Physiotherapy (TP) or TP combined with Functional Massage (FM). Interventions were delivered at equal dosage (total eight weeks, 2 days per week, 45 minutes/day) in the same environment. The severity of spasticity was measured with Modified Ashworth Scale (MAS), and functional level and gross motor function were quantified according to GMFCS and Gross Motor Function Measure (GMFM), respectively. Results: When the pre-therapy and post-therapy data covering GMFM and hip adductors, hip flexors, hamstrings and calf muscles spasticity score of the both groups were compared, no statistically significant difference was determined in the hip flexor spasticity score of the control group (p>0.05), while considerable differences were defined in the hip flexors spasticity score of the experimental group (p<0.05). Improvements on MAS belonging to other three muscle groups and on GMFM score were similar in both groups (p>0.05). Conclusion: In conclusion, it was identified that FM combined with TP is effective in treating spasticity and in improving some parameters related to motor function in children with CP.

Amaç: Bu çalışmanın amacı; fonksiyonel masajın serebral palsili (SP) çocukların alt ekstremite spastisite şiddetine ve kaba motor fonksiyonlarına etkilerini araştırmaktı. Yöntem: Çalışmaya iki farklı rehabilitasyon merkezinden, iletişim becerisi olan (İletişim Becerileri Sınıflandırma Sistemine göre iletişim becerileri I-III arasında), fonksiyonel seviyeleri Kaba Motor Fonksiyon Sınıflandırma Sistemi’ne (KMFS) göre I-IV arasında değişen, hiç ameliyat geçirmemiş ve yaşları 5-12 yaş arasında değişen 20 SP‘li çocuk dahil edildi. Çalışmaya dahil edilen çocuklar kontrol veya araştırma gruplarına sırasıyla sadece Konvansiyonel Fizyoterapi (KF) veya KF’ye ek olarak Fonksiyonel Masaj (FM) almak üzere rastgele dağıtıldı. Uygulamalar gruplara aynı ortamda ve eşit dozlarda verildi (toplam sekiz hafta, haftada 2 gün, günde 45 dk). Spastisite şiddeti Modifiye Ashworth Skalası (MAS), fonksiyonel seviye ve kaba motor fonksiyonlar sırasıyla KMFS ve Kaba Motor Fonksiyon Ölçütü (KMFÖ) ile değerlendirildi. Bulgular: Her iki gruba ait terapi öncesi ve terapi sonrası KMFÖ, kalça fleksörleri, adduktörleri, hamstringler ve baldır kaslarının spastisite skorlarını kapsayan veriler karşılaştırıldığında, kontrol grubuna ait kalça fleksörleri spastisite skorunda herhangi bir fark bulunmazken (p>0.05); araştırma grubuna ait kalça fleksörleri spastisite skorunda iyileşme saptandı (p<0.05). MAS’daki diğer üç kas grubuna ait spastisite skorunda ve KMFÖ skorundaki değişimler her iki grup için benzerdi. Sonuç: Sonuç olarak, SP’li çocuklarda FM’nin KF ile kombinasyonu spastisitenin tedavisinde ve motor fonksiyonlarla ilgili bazı parametreleri iyileştirmede etkili olduğu sonucuna varılmıştır
Fonksiyonel masajın serebral palsili çocuklarda spastisite ve motor fonksiyon üzerine etkileri: rastgele kontrollü çalışma